1991
DOI: 10.1002/aic.690370206
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of reaction in a partially wetted catalytic pellet

Abstract: (e.g., Harold and Ng, 1987;Funk et al., 1988Funk et al., , 1989

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…This critical fraction decreases with increasing liquid ow rate. At the highest liquid ow rate, corresponding to operation in the pulse ow regime, the conversion rate is independent of x-AMS for x-AMS > 0.02 which agrees with the results reported by Germain et al 32 , Snider and Perona 33 , Funk et al 34 and Cini and Harold 30 . They, however, all operated their reactor in the trickle ow regime.…”
Section: Performance Of Structured Packings In Trickle-bed Reactorssupporting
confidence: 82%
See 1 more Smart Citation
“…This critical fraction decreases with increasing liquid ow rate. At the highest liquid ow rate, corresponding to operation in the pulse ow regime, the conversion rate is independent of x-AMS for x-AMS > 0.02 which agrees with the results reported by Germain et al 32 , Snider and Perona 33 , Funk et al 34 and Cini and Harold 30 . They, however, all operated their reactor in the trickle ow regime.…”
Section: Performance Of Structured Packings In Trickle-bed Reactorssupporting
confidence: 82%
“…This effect has also been observed in the literature 31,34,35 and can be explained by partial wetting. It is thought that at the wetted part external mass transfer is the rate limiting process, whereas the hydrogen supply to the externally non-wetted part is conceived to proceed very fast and consequently the internal diffusion limited chemical reaction is rate limiting in this case.…”
Section: Spherical Catalyst Particlessupporting
confidence: 65%
“…This is evidenced by the large number of literature studies (Babcock et al, 1957;Satterfield et al, 1969;Germain et al, 1974;White et al, 1974;Morita and Smith, 1978;Herskowitz et al, 1979;Turek and Lange, 1981;El-Hisnawi et al, 1982;Funk et al, 1991;Cini and Harold, 1991;among others). These studies demonstrate that the liquid-phase/catalytic reaction is mass-transport-limited with respect to sparingly soluble hydrogen (in Cini and Harold (1991) showed that for a sufficiently low AMS concentration the rate is positiveorder in AMS.…”
Section: Selection Of the Model Reaction Systemsmentioning
confidence: 83%
“…Indeed, as Table 2 shows, AMS (cumene) boils at 165 (152)"C and has a vapor pressure of only 6.2 (11.0) torr at 40°C, for example. Nevertheless, subtle features in the single-pellet experimental study of Funk et al (1991) demonstrate that the moderate exothermic heat of reaction can lead to some vaporization from the nonwetted surface of the partially wetted pellet. Thermal effects can be quite dramatic under some conditions, as in the aforementioned Germain et al (1974) and McManus et al (1993) studies.…”
Section: Selection Of the Model Reaction Systemsmentioning
confidence: 98%
See 1 more Smart Citation